The Glossa Ordinaria on Romans - Woodward, Michael S.; Project Muse. (Medieval Institute Publications, Western Michigan University, Kalamazoo, 2011)
The Gloss on Romans is a collection of sources from many periods and places, which accounts for its inconsistencies. And this is what gives the Gloss much of its charm ... The twelfth century was an age of gathering sources and commentaries, in theology (Lombard's Sentences), canon law (Gratian's Decretum), and biblical studies (the Glossa ordinaria). Education began to flourish into what would become universities, where the master's role was to elucidate traditional, authoritative texts. And chief among these was the Bible, not standing alone but with the accompanying Gloss." - from the introduction.
Cover -- Halftitle -- Series -- Title -- Copyright -- Contents -- Abbreviations -- Introduction -- Prefatory Material -- Chapter 1 -- Chapter 2 -- Chapter 3 -- Chapter 4 -- Chapter 5 -- Chapter 6 -- Chapter 7 -- Chapter 8 -- Chapter 9 -- Chapter 10 -- Chapter 11 -- Chapter 12 -- Chapter 13 -- Chapter 14 -- Chapter 15 -- Chapter 16 -- Notes
Kommentar mit eingefügtem Bibeltext.
Description based on print version record.
JSTOR
Keywords: Bible. -- Commentaries; Bible; Bibel; Römerbrief.; Biblical Commentary; RELIGION; Glosse; Electronic books; Commentaries; Kommentar